SURFING ON PHYSICAL EDUCATION CURRICULUM AND THE IMPACT ON STUDENT’S WELL-BEING - Bruno Silva; Gonçalo Cruz; Renato Bentes; Ricardo Franco Lima (Journal of Physical Education)
ABSTRACT Physical Educations classes represent a unique opportunity to develop motor competence, sports skills and foster healthy life. Blue spaces environments provide an alternative location for high-quality outdoor educational experiences. Throughout, surfing is an aquatic outdoor sport, that takes place in the natural setting, proved as an important learning and therapeutic approach. The aim of this research was to analyze the importance of surfing in Physical Education (PE) classes as a support of children and adolescent’s well-being. A total of 190 students (80 girls) participated in this study and were assessed at baseline and after 6 weeks of surfing practice as part of a PE curriculum, regarding the impacts on well-being and socialization. Analyzing the two moments, the most valued questions were Q5(4.39±0.827; 4.52±0.791) and Q14(4.60±0.716; 4.47±0.808). The exploratory factor analysis results in 3 categories (Individual Expectations; Self-Confidence; Socialization in Surfing), which explain 62.79% of the total variance. The factor Individual Expectation was the most significant and Self-Confidence had the most significant increase. Surfing as part of the PE curriculum can be considered a safe activity, an important mediator for making new friends and being part of a group with important short-term effects on self-confidence, especially in adolescents.